Study of Interaction between Vitamin C and Nickel () Ion using a Polarographic Methods - Al Rufaie, Elham; Abdel Kalik Hussain, Mohamed (Iraqi Journal of Science, 2023)
The Polarographic study of the interaction between ascorbic acid and Ni+2 was carried out at dropping mercury electrode [DME] . This study included the determination of the kinetic parameters (kfh ,n) and thermodynamic parameters such as enthalpy change (H), free energy change (G) and entropy change (S) of Ni+2 complexes with ascorbic acid in 0.1 M KCl solution over the temperature rang of (294-309)K. The electrode processes were irreversible and diffusion controlled.